The art of writing drama - Wandor, Michelene (London : Methuen Drama, 2008)
Presents an approach to drama writing, and discusses drama in education, performance theory, the roles of the director and performer, stage directions, women dramatists, and more; and features practical workshop guidelines.
Includes bibliographical references.
Adult
Keywords: Drama -- Technique; Playwriting; Drama -- Technique